2022
DOI: 10.1021/acssynbio.2c00480
|View full text |Cite
|
Sign up to set email alerts
|

Unusual Class I Lanthipeptides from the Marine Bacteria Thalassomonas viridans

Abstract: A novel class I lanthipeptide produced by the marine bacterium Thalassomonas viridans XOM25T was identified using genome mining. The putative lanthipeptides were heterologously coexpressed in Escherichia coli as GFP–prepeptide fusions along with the operon-encoded class I lanthipeptide modification machinery VdsCB. The core peptides, VdsA1 and VdsA2, were liberated from GFP using the NisP protease, purified, and analyzed by collision-induced tandem mass spectrometry. The operon-encoded cyclase and dehydratase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(33 citation statements)
references
References 27 publications
(75 reference statements)
0
33
0
Order By: Relevance
“…Furthermore, groups of the partially dehydrated peptides were observed by MALDI-TOF MS with multiple increases of 307 Da, which suggests the addition of glutathione (GSH) to the reactive dehydroamino acids of the dehydrated peptides. 30,34,35 This result showed that, like the observations with epilancin 15X, the LanB dehydratases from these BGCs cannot effectively utilize the tRNA Glu /GluRS system from E. coli to activate Ser or Thr residues by glutamylation. Indeed, the tRNA Glu sequence in E. coli at the critical recognition positions is divergent compared to those of Chryseobacterium and Runella (Fig.…”
Section: Heterologous Expression Of New Class I Lanthipeptides Derive...mentioning
confidence: 56%
See 4 more Smart Citations
“…Furthermore, groups of the partially dehydrated peptides were observed by MALDI-TOF MS with multiple increases of 307 Da, which suggests the addition of glutathione (GSH) to the reactive dehydroamino acids of the dehydrated peptides. 30,34,35 This result showed that, like the observations with epilancin 15X, the LanB dehydratases from these BGCs cannot effectively utilize the tRNA Glu /GluRS system from E. coli to activate Ser or Thr residues by glutamylation. Indeed, the tRNA Glu sequence in E. coli at the critical recognition positions is divergent compared to those of Chryseobacterium and Runella (Fig.…”
Section: Heterologous Expression Of New Class I Lanthipeptides Derive...mentioning
confidence: 56%
“…Glutathionylation of reactive dehydroamino acids in lanthipeptides is often observed during heterologous expression in E. coli, 30,34,35 impeding further structural and biological investigations. Efforts to optimize expression conditions to prevent glutathionylation, such as using different E. coli strains or changing the expression temperature, failed to prevent glutathionylation.…”
Section: Deglutathionylation Utilizing Lancl Enzymesmentioning
confidence: 99%
See 3 more Smart Citations